The Berenstain bears come clean for school - Berenstain, Jan; Berenstain, Michael (New York : HarperFestival, 2011)
On the first day of school, Brother and Sister Bear learn how to stop germs from spreading.
Ages 3-7.
Keywords: Children's stories